Comparing usefulness of immediate postpartum intrauterine contraceptive device among the women undergoing caesarean or vaginal insertion - Nirja Sharma (Barpeta Obstetrics and Gynaecological Society, 2022)
Background: During the first year postpartum only 26% of the women use any method of family planning. Using IUCD in the immediate post-partum period can offer an effective and safe method for spacing and limiting births. Objectives: The objectives of the present study were to evaluate and compare the safety and efficacy of PPIUCD inserted at caesarean versus vaginal delivery. Methods: This is a prospective study conducted at Govt. Medical College Shivpuri and District Hospital Shivpuri from February 2016 to February 2017. A total of 100 patients with caesarean and vaginal deliveries had PPIUCD insertions and they were followed up for one year. The outcome measure analyzed were safety measures (menstrual irregularities, vaginal discharge, pelvic infection, perforation, failure, expulsion and removal). Results: PPIUCD is an effective intervention in both caesarean and vaginal delivery with no significant differences in safety (menstrual complaints, fever and vaginal discharge; p>0.05) and efficacy depending on the route of insertion as the majority of the clients were satisfied with PPIUCD insertion (65.7%) with only 4.5% unsatisfied with the procedure. There was no case of perforation or failure and no significant risk of infection in either group (only 1.8% vaginal discharge). Spontaneous expulsion occurred in three cases inserted by vaginal route. Missing string incidence is high in the caesarean group (48.5%) compared to vaginal insertion (25%) (p= 0.02). Conclusion: PPIUCD is a safe effective and convenient method of contraception and should be encouraged in both vaginal and caesarean deliveries.